Education for Sustainable Development: The Bekarang Tradition as an Educational Tool for Teaching Biology - Agusta, Erie; Apriana (Journal of Pedagogy and Education Science, 2025)
The Bekarang tradition, a communal fishing practice in South Sumatra, reflects sustainable river management but faces threats from modernization. Preserving it through education requires aligning its cultural meaning with learning contexts. This qualitative study examines the significance of Bekarang and its potential integration into Biology education through interviews with cultural and pedagogical experts, as well as a literature review. Thematic analysis identified key themes for contextualizing Biology learning, followed by interpreting indigenous science through socio-scientific issues. Findings reveal that the Bekarang embodies a blue economy philosophy, addressing SDGs by fostering cooperation, responsibility, and environmental stewardship. It aligns with Biology topics like ecosystem, conservation, and biodiversity, and suits pedagogical models. This study highlights the Bekarang’s value as an educational tool for culturally rooted and sustainable science learning.